How Corporate Social Responsibility Engagement affects Corporate Financial Performance in the UK - Yang, Yating (2020)
This study analyses the effects of CSR on corporate financial performance (CFP) in light of recent requests for identifying Corporate Social Responsibility (CSR) and its impact on the shareholder's wealth. This research includes 132 listed companies in the UK of FTSE 350 in a three-year period between 2016 and 2018. In terms of quantifying CSR, we introduced CSR engagement in those companies using dummy variables, while we chose profitability and shareholder value to measure CFP with the indicator of return on assets (ROA) and Tobin’s Q respectively. According to its accounting-based and market-based measurements, two econometric models are constructed by controlling firm size, firm age, leverage, R&D research, and sales revenues. CSR's impact on firm economic performance is examined through STATA's correlation and regression analysis, and the results obtained indicate that there is no statistically significant relationship identified between CSR and financial performance of companies, regardless of two models. This finding is partly in line with the initial assumptions and several previous studies denying any relationship between them in the past two decades in Europe, however, contrary to the resource-based view and other past papers. This study contributes to managers as well as other stakeholders regarding their decision making related to the CSR by explaining numerous possible CSR biases. Furthermore, it broadens the study of the effect of CSR on firm value in the world in academics and fills the research gap in the UK, despite many previous studies that can be found in Europe.